Application of the Snowball Throwing Method to Enhance the Critical Thinking of 5th Grade Students in The Learning of Akidah Akhlak at MI PSM Gedoro - Khotimah, Khusnul; Nurhasanah, Muwahidah (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2024)
The teaching method used in the classroom plays a crucial role in a child's learning process, especially in developing their critical thinking skills. However, in practice, there are still some educational institutions, particularly in madrasahs, that have not fully embraced a variety of teaching methods in the classroom instruction. Therefore, this research aims to explore the positive impact of implementing the snowball throwing method in enhancing the critical thinking skills of fifth-grade students at the Islamic Elementary School (MI) PSM Gedoro. The snowball throwing method is a collaborative learning approach that encourages group work and active discussion, with a focus on developing critical thinking skills. The method involves four stages: Planning, Socialization, Implementation, and Evaluation. The research results indicate that students who applied the snowball throwing method experienced a significant improvement in their critical thinking skills. This method also facilitates collaboration, problem-solving, and reflection, all of which play a crucial role in enhancing students' critical thinking skills.